Comments on the Interpretation of Game Theory - Rubinstein, Ariel (Econometrica, 1991)
The paper is a discussion of the interpretation of game theory. The first half of the paper deals with the notion of "strategy". The paper endorses the view that equilibrium strategy describes a player's plan of action, as well as those considerations which support the optimality of his plan rather than being merely described as a "plan of action". In the second half of the paper it is argued that a good model in game theory has to be realistic in the sense that it provides a model for the perception of real life social phenomena. It should incorporate a description of the relevant factors involved, as perceived by the decision makers. Copyright 1991 by The Econometric Society.